Left Hand Dominance Affects Supra-Second Time Processing - Vicario, Carmelo M.; Bonnì, Sonia; Koch, Giacomo (Frontiers in Integrative Neuroscience, 2011)
Previous works exploring the brain functions of left-handed and right-handed people have shown variances in spatial and motor abilities that might be explained according to consistent structural and functional differences. Given the role of both spatial and motor information in the processing temporal intervals, we designed a study investigating timing abilities in left-handed subjects. To this purpose left-handed and right-handed subjects were asked to perform a time reproduction of sub-second vs. supra-second time intervals with their left and right hand. Our results show that left-handed participants sub-estimated the processing of the supra-second intervals, independently of the hand used to perform the task, while no differences were reported for the sub-second intervals. These results are discussed according to recent advances on suprasecond motor timing research as well as emerging evidences which suggest a linear representation of time with a left-to-right displacing.